EFFECTIVENESS ABOUT TECHNIQUES OF PUZZLE GAMES IN UNDERSTANDING THE CONCEPT WHEN LEARNING SOCIAL SCIENE AT JUNIOR HIGH SCHOOL OF 40 BANDUNG (Quasi Experimental Study at Junior High School of 40 Bandung) - Erladini, Yosefin Candra (International Journal Pedagogy of Social Studies, 2017)
Abstract-The present study was motivated by the authorâ€™s eagerness to investigate the effectiveness aboutÂ  techniques of puzzle games in understanding the concept when learning social sciene at Junior High School of 40 Bandung. This research was aimed to explain the ability of understanding the concept when learning social sciene before and after applying the techniques of puzzle games, explaining the effect from techniques of puzzle games when learning social sciene, and showing the effectiveness from techniques of puzzle games when learning social sciene. The study employed quasi experimental study with the design of pretest-posttest control group. According to hypothesis test showed the difference between the ability of understanding the concept social sciene at experimental class and the capability at controlled class, after the experimental class being given techniques of puzzle games treatment when learning social sciene. Consequently, it can be conclude that implementing the techniques of puzzle games was really effective to be used in understanding the concept when learning social sciene.Keywords: Techniques of puzzle games, The understanding of concept, Sosial sciene.